PREVALENCE AND ASSOCIATED FACTORS OF ASTHMA, ALLERGIC RHINITIS AND ECZEMA IN TURKISH CHILDREN AND ADOLESCENTS - Mücahide Gökçen Gökalp; Mithat Kıyak; Fuat Erel (Sabuncuoglu Serefeddin Health Sciences, 2026)
Abstract Background: Asthma, allergic rhinitis, and eczema are among the most common chronic diseases of childhood, and their prevalence varies across regions. Understanding the distribution of these conditions in Türkiye is essential for effective pediatric health planning, particularly in light of environmental and lifestyle changes observed over the past decade. Objective: This study aimed to determine the prevalence of allergic diseases and associated risk factors among 6–7 and 13–14-year-old schoolchildren in Balıkesir, located in Western Türkiye, and to compare the findings with recent national data. Methods: The study was conducted in 2013 using a cross-sectional survey design based on the validated Turkish version of the International Study of Asthma and Allergies in Childhood (ISAAC) Phase I questionnaire. A total of 3,647 students were selected from 26 schools through a stratified cluster sampling method according to socioeconomic status. Results: In the 6–7 and 13–14 age groups, lifetime wheezing prevalence was 31.5% and 19.3%, 12-month wheezing prevalence was 19.8% and 12.8%, and physician-diagnosed asthma was 11.1% and 7.1%, respectively. Lifetime rhinitis prevalence was 37.1% and 35.7%, physician-diagnosed allergic rhinitis was 15.4% and 14.8%, and physician-diagnosed atopic dermatitis was 8.8% and 6.7%, respectively. A family history of allergy, low socioeconomic status, and environmental exposures were identified as significant associated factors. Conclusion: The prevalence of allergic diseases in Balıkesir was found to be higher than in earlier Turkish ISAAC studies and remained comparable to national surveys conducted in the last decade. These findings highlight the ongoing burden of pediatric allergic diseases in Türkiye and emphasize the need for early diagnosis, prevention, and follow-up strategies tailored to regional characteristics. Keywords: Asthma, allergic rhinitis, eczema, prevalence, pediatric allergies, schoolchildren, Türkiye, ISAAC